Medicinal Plants as a Natural Greener Biocontrol Approach to “The Grain Destructor” Maize Weevil (Sitophilus zeamais) Motschulsky - Ompelege Jacqueline Phokwe; Madira Coutlyne Manganyi (Plants, 2023)
According to the United Nations (UN), the global population may skyrocket to 9.8 billion people in 2050 and 11.2 billion in 2100, placing an overwhelming burden on food security as the world will have to meet this growing demand. Maize is the largest staple grain crop produced in developing countries. The maize weevil, Sitophilus zeamais, is one of the most destructive post-harvest pests of stored cereals and grains. The maize weevil contributes up to 40% of total food-grain losses during storage, mainly in developing countries. Current synthetic pesticides are ineffective, and, moreover, they raise serious environmental safety concerns as well as consumer health hazards. Drawing from past oversights and current environmental realities and projections, the global population has been switching to green living by developing sustainable strategies. In our context, these new greener strategies include the utilization of medicinal plants to control maize weevil infestation, which unlocks unlimited innovative possibilities, and, thus, improves the yield, quality, and safety of maize. Medicinal plants are less toxic, easily biodegradable, and capable of protecting grain from pests. This paper systematically outlines the literature on host plants as well as the feeding and associated diseases of the maize weevil. In light of this, we cement medicinal plants as excellent candidates in the pursuit of greener, sustainable, more potent, and cost-effective pesticides.